COMPARISON AND VALIDATION OF TRMM SATELLITE PRECIPITATION ESTIMATES AND DATA OBSERVED IN MATO GROSSO DO SUL STATE, BRAZIL - Abreu, Marcel; Souza, Amaury; Lins, Taynã Maria Pinto; Júnior, José; Oliveira, Soetânia; Fernandes, Widinei Alves; Almeida, Laura Thebit de; Torsen, Emmanuel (Revista Brasileira de Climatologia, 2020)
Precipitation is the most important variable in the hydrological cycle and can be estimated through remote sensing. Thus, the use of estimated satellite data has been an alternative to the absence of meteorological stations. The objective of this study was to evaluate the rainfall data of the TRMM satellite 3B43 product with data from the ANA site in the state of Mato Grosso do Sul for the period 1998 to 2013. For this purpose, it was used for the comparison of data from of the ANA site (OBS) and those estimated by the satellite, the following statistical indicators: Bias, Mean Square Error (EMQ), Pearson correlation coefficient (CC). For the most part, the satellite estimation data were satisfactory, especially for the months from March to November. The results indicate that the use of the estimated satellite data may be an alternative to the use of meteorological stations.